ʻĒkkasān prakō̜p kānsammanā thāng wichākān rư̄ang kānbō̜rihānngān dān phatsadu læ kānchotchœ̄i khā ngān kō̜sāng (khā K) : rawāng wanthī 20 thưng wanthī 21 Mīnākhom 2552 na Rōngrǣm Daimō̜n Phlāsā (Surāt Thānī) (Samākhom Nakbō̜rihān Phatsadu hǣng Prathēt Thai, 2009)
Papers for academic conference on commonity management and compensation for the cost of construction work, held on March 20-21, 2009, at Diamond Plaza Hotel, Surat Thani Province, Southern Thailand.